Green synthesis, characterization and in-vitro bioactivities of gold nanoparticles mediated by turmeric crude extract and curcumin - Abbas, Sameera (2021)
In the present study, green synthesis and characterization of gold nanoparticles (GNPs) using the ethanolic crude extract of turmeric (Tur-CE) and curcumin (Cur) have been described. Antioxidant, anticholinesterase (anti-ChE), and antiurolithiatic activities of the extracts and the GNPs were tested in vitro and Pearson’s correlation analysis was performed. The optimization of GNP synthesis was performed using Tur-CE (2 % of 10 mg/mL) and curcumin (0.5 % of 10 mg/mL) at a reactant ratio (Tur-CE or Cur: HAuCl4) of 1:4, pH 6 and 12 of Tur-CE and curcumin, respectively. The other conditions include the concentration of HAuCl4 (0.25 mM) and different reaction temperatures (25, 40, 55 and 70 °C). FESEM analysis of GNPs synthesized at 25 °C by using Tur-CE (TP6.25) and curcumin (CP12.25) revealed the size range of 11-40 and 31-100 nm, respectively. The highest antioxidant activity was recorded for TP6.25, that is, 82.60, 79.60 and 12.22 % for ABTS, DPPH and FRAP, respectively, and anti-ChE activity at 75.10 and 74.33 % for AChE and BChE, respectively, However, the maximum % I for ABTS, DPPH, and FRAP, that is, 87.20, 86.00 % and 19.36 µg FSE, respectively, was shown by positive control ascorbic acid, and for AChE and BChE inhibition, 86.69 and 89.30 %, respectively, by galanthamine. TP6.25 also showed good antiurolithiatic activity as indicated by absorbance value of 0.198 and 0.164 in nucleation and crystallization assays, respectively. Pearson correlation revealed a positive correlation between antioxidant and anti-ChE, as well as antioxidant and antiurolithiatic activities. The GNPs were haemocompatible as TP6.25 and CP12.25 induced 1.172 and 0.763 % haemolysis, respectively, at the highest concentration of 500 µL in haemolysis assay compared to 99.85 % haemolysis by positive control. In conclusion, Tur-GNPs and Cur-GNPs possess good antioxidant, anticholinesterase and antiurolithiatic properties, in addition to being non-haemolytic, may be an option to further explore their therapeutic potential as antioxidant, anticholinesterase, and antiurolithiatic agents in neurodegeneration and urolithiasis.